An update on risk factors for drug-induced arrhythmias. Issue 1 (2nd January 2016) - Vlachos, Konstantinos; Georgopoulos, Stamatis; Efremidis, Michael; Sideris, Antonios; Letsas, Konstantinos P
Abstract : A variety of drugs, either anti-arrhythmics or non-antiarrhythmics, have been associated with drug-induced arrhythmias. Drug-induced arrhythmias are usually observed in the presence of long QT interval or Brugada electrocardiographic pattern. Clinical risk factors, such as female gender, structural heart disease, metabolic and electrolyte abnormalities, bradycardia and conduction disease, increased drug bioavailability, and silent channelopathies act as ''effect amplifiers'' which can make an otherwise relatively safe drug dangerous with regard to risk for polymorphic ventricular tachycardia in the setting of QT interval prolongation. A drug-induced type 1 electrocardiographic pattern of Brugada syndrome is considered highly proarrhythmic. Specific electrocardiographic markers including the corrected QT interval, QRS duration, Tpeak –Tend /QT ratio, and others may predict the risk of arrhythmias in both situations. The present review highlights on the current clinical and electrocardiographic risk factors for prediction of drug-induced arrhythmias.